Application of the Richards function to serum antibody titration - Kovács, Ágnes; Papp, Krisztián; Prechl, József; Pfeil, Tamás (Frontiers in Immunology, 2025)
Conventional approaches to the titration of serum antibody binding use mid-point or end-point titers that are in a relative space and are therefore difficult to standardize. Here we propose the use of the thermodynamic titer, which, under appropriate measurement conditions, is a universal measure of the thermodynamic activity of serum antibodies. We show that the interpretation of the generalized logistic function as applied to biochemical binding events is possible using analogies to relative and absolute growth rates and size, which applies to the products of the reaction. Such deeper interpretation reveals the biological meaning of the asymmetry parameter of the function as a proportionality factor to ideal binding conditions. The use of a universally applicable and thermodynamically meaningful serum antibody titer could improve systematic mapping and understanding of antibody function.